Cultivate research for the benefit of society - Nor Salwana, Mohammad Idris (2022)
PEKAN, 4 October 2022 – In enhancing the role of the university, Universiti Malaysia Pahang (UMP) needs to advance research and harness the strengths in the intellectual field to impact the community, technology, economy and society.